2010
DOI: 10.1682/jrrd.2009.03.0031
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of controlling prosthetic hand using sonomyography signal in real time: Preliminary study

Abstract: Abstract-The morphological changes of muscle can be accurately detected by sonography, a process we have termed sonomyography (SMG). This article investigates the feasibility of using muscle thickness deformation SMG as a new signal source to control a prosthetic hand in real time. Thickness deformation SMG of the extensor muscle was measured by a block-matching algorithm during wrist extension-flexion; the amplitude of the deformation was used to control the prosthetic hand. We compared various fast-search al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 35 publications
(73 reference statements)
0
33
0
2
Order By: Relevance
“…Out of these papers, we classified the articles into three folds (15), subdivided into: (i) sensor development (5), (ii) sensor effects on MMG (5) and (iii) sensor comparison for MMG assessment (5). II) MMG signal processing (8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of these papers, we classified the articles into three folds (15), subdivided into: (i) sensor development (5), (ii) sensor effects on MMG (5) and (iii) sensor comparison for MMG assessment (5). II) MMG signal processing (8).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a proper diagnosis is essential in order to identify and treat these muscle disorders. Consequently, many researchers have continued to explore suitable techniques, which include electromyogram (EMG) [1], [2], myokinetic (MK) therapy [3], sonomyogram (SMG) [4], [5], tensiomyogram (TMG) [6], [7], and mechanomyogram (MMG) [8], [9].…”
mentioning
confidence: 99%
“…The use of this synchronised recording method may be extended to diagnosis and to evaluation of therapies (7,(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies propose the use of ultrasound scanners [82,83,84,166] to measure changes in muscle thickness for the control of prosthetic devices. This method is known as sonomyography (SMG).…”
Section: Muscle Vibrationmentioning
confidence: 99%
“…A recent study by Gonzalez and Castellini [84] shows that a linear relationship also exists between specific image features and fingertip forces. Furthermore the study by Shi et al [166] shows that SMG can be implemented in real-time using a two-dimensional logarithmic search algorithm. While it has been demonstrated that SMG could be potentially used for the control of active prosthetic devices, the current system used for the SMG measurements (i.e., standard ultrasound scanner) is not suitable for practical implementation because it is expensive and cumbersome [83].…”
Section: Muscle Vibrationmentioning
confidence: 99%